The Effect of Receptie Theory on Legal Concept of â€œAdat Barenti Lako Syaraâ€™, Syara Barenti Lako Kitabullahâ€ - Dianto, Dianto (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Receptie theory of Snouck Hurgonje's thought requires that Islam be valid if it has been perceived by customary law. The perception of a starting point between Islamic law and customary law was mediated by Syahrial Abbas with his split bamboo theory. However, the concept ofÂ